Information Management System (IMS) for Gender Mainstreaming in Higher Education: The Case of the University of Dar Es Salaam, Tanzania - Msuya, Jangawe; Mukangara, F. (My University, 2007)
Information Management System (IMS) is an essential tool in supporting the provision of information needed for planning and decision making in any organization. Proper IMS facilitates the smooth flow of information both vertical and horizontal. This paper presents the findings of a survey on information needs of the Gender Development Programme Committee (GDPC) of the University of Dar es Salaam that was carried out with a view to developing appropriate Information Management System. A total of 180 respondents were involved in this study, comprising of students, faculty members, administrative staff and the Senior University Management. Interview, questionnaire, in-depth interview and focus group discussions were the main data collection methods. The study revealed that GDPC generates a lot of information on its activities such as gender based research opportunities, undergraduate female scholarships and gender sensitization workshops. Information on these activities is highly needed by the stakeholders but there is no organized vertical and horizontal system of information flow. The study recommends the establishment of GDPC's information dissemination mechanism, including developing databases on GDPC activities, creation of a website, establishing a documentation unit and transforming GDPC to a full fledged Gender Centre.
Full text can be accessed at http://www.ajol.info/index.php/udslj/article/view/26666